Learn Algorithmic Trading : Build and Deploy Algorithmic Trading Systems and Strategies Using Python and Advanced Data Analysis - Donadio, Sebastien (Packt Publishing, Limited, 2019)
This book will provide knowledge and hands-on practical experience required to build a good understanding of how modern electronic trading markets and market participants operate. You will learn how to design, build and operate all the components required to build a practical and profitable algorithmic trading business using Python.